Voice disorders in persons with Parkinson's disease: characteristics, assessment and treatment - Paunović, Verica; Petrovic Lazic, Mirjana; Vukovic, Mile (Medicinski časopis, 2024)
Parkinson's disease is a progressive neurodegenerative disease that is primarily manifested by impairment of motor skills and speech. Although voice disorders characterize the speech of people with Parkinson's disease, they are still not sufficiently clarified from a clinical point of view. With that in mind, the aim of this paper is to present the characteristics of the voice in Parkinson's disease, as well as assessment and treatment methods, based on a review of the available literature.The search of relevant literature was performed on the basis of databases of scientific research works PubMed, KoBSON, Science Direct, Google Scholar, as well as works available in paper version. Papers published from 2000 until today dedicated to voice disorders in people with Parkinson's disease were analyzed.The results show that voice disorders occur within the clinical picture of Parkinson's disease and that the symptoms progress with the progression of the disease. The basic characteristics of the voice are monotony, hypophonic and hoarseness. Due to the great impact of voice disorders on speech intelligibility, different methods of speech therapy are used in the treatment of these patients. Lee Silverman's method is the best known and most effective method of phonation and respiration rehabilitation in people with Parkinson's disease.Based on a review and analysis of the available literature, it is evident that vioice disorders are one of the significant simptoms of this disease, and that speech therapy assessment and voice treatent is an essential element of the rehabilitation of these people.
Keywords: Parkinson's disease; voice disorders; voice assessment; voice treatment